Expression of eosinophil β chain-signaling cytokines receptors, outer-membrane integrins, and type 2 inflammation biomarkers in severe non-allergic eosinophilic asthma - Kalinauskaite-Zukauske, Virginija; Januskevicius, Andrius; Janulaityte, Ieva; Miliauskas, Skaidrius; Malakauskas, Kestutis (BMC pulmonary medicine, 2019)
Background Severe non-allergic eosinophilic asthma (SNEA) is a rare asthma phenotype associated with severe clinical course, frequent exacerbations, and resistance to therapy, including high steroid doses. The key feature is type 2 inflammation with predominant airway eosinophilia. Eosinophil maturation, activation, survivability, and recruitment are mainly induced by interleukin (IL)-3, IL-5 and granulocyte–macrophage colony-stimulating factor (GM-CSF) through their receptors on eosinophil surface and related with integrins activation states. The aim of the study was to estimate the expression of eosinophil β chain-signaling cytokines receptors, outer-membrane integrins, and serum-derived type 2 inflammation biomarkers in SNEA. Methods We examined 8 stable SNEA patients with high inhaled steroid doses, 12 steroid-free patients with non-severe allergic asthma (AA), 12 healthy subjects (HS). Blood eosinophils were isolated using Ficol gradient centrifugation and magnetic separation. Eosinophils were lysed, and mRNA was isolated. Gene expressions of IL-5Rα, IL-3Rα, GM-CSFRα, and α4β1, αMβ2 integrins were analyzed using quantitative real-time reverse transcription polymerase chain reaction. Type 2 inflammation activity was evaluated measuring exhaled nitric oxide concentration (FeNO) collected with the electrochemical sensing device. Serum IL-5, IL-3, GM-CSF, periostin, chemokine ligand (CCL) 17 and eotaxin concentrations were assessed by enzyme-linked immunosorbent assay. Results Eosinophils from SNEA patients demonstrated significantly increased gene expression of IL-3Rα, IL-5Rα and GM-CSFRα as well as α4, β1 and αM integrin subunits compared with the AA group. The highest IL-5 serum concentration was in the SNEA group; it significantly differed compared with AA and HS. GM-CSF serum levels were similar in the SNEA and AA groups and were significantly lower in the HS group. No differences in serum IL-3 concentration were found among all groups. Furthermore, serum levels of eotaxin, CCL17 and FeNO, but not periostin, differed in all groups, with the highest levels in SNEA patients. Conclusions Eosinophil demonstrated higher expression of IL-3, IL-5, GM-CSF α-chain receptors and α4, β1, αM integrins subunits in SNEA compared with the AA group. Additionally, SNEA patients had increased serum levels of IL-5, eotaxin and CCL-17. Trial registration ClinicalTrials.gov Identifier NCT03388359.